Efficacy of dexamethasone for lung maturity in preterm delivery in association with lamellar bodies count - Ni Made Sumiartini; Hendra Santoso; Wayan Retayasa; Made Kardana (Paediatrica Indonesiana, 2007)
Background Organ immaturities in preterm infants may result inperinatal death. One of the diseases is respiratory distress syndrome(RDS) which is caused by lung immaturity. Dexamethasone is oftenused to accelerate maturity of infant lungs.Objective To determine the efficacy of dexamethasone on lungmaturity measured by lamellar bodies count.Methods A quasi experimental study was done at PerinatologyDivision, Department of Child Health, Medical School, UdayanaUniversity, Sanglah Hospital, Denpasar. We recruited 72 subjects;36 subjects were given four times intramuscular dexamethasone5 mg every twelve hours before delivery. Thirty six subjects whodid not receive dexamethasone belonged to control group. Infants’lungs maturity assessment was performed using lamellar bodiescount taken from amniontic fluid.Results The gestational age ranged between 28 to 36 weeks, withthe mean gestational age in dexamethasone group was 32.2 (SD1.76) weeks and that in control group was 31.7 (SD 2.65) weeks.The efficacy of dexamethasone therapy on lung maturity wassignificant with Fisher’s exact test P<0.0001, 95%CI 2.546;11.173. Using multivariate logistic regression analysis, there wassignificant correlation between dexamethasone and lung maturitymeasured by lamellar bodies count [OR=239.39; P<0.0001,95%CI 22.12;526.53].Conclusion Administration of dexamethasone in pregnantwomen during preterm delivery significantly improves lungmaturity measured by lamellar bodies count.